Efficacy and safety of ibrutinib in Japanese patients with relapsed or refractory mantle cell lymphoma. Issue 12 (25th November 2016) - Maruyama, Dai; Nagai, Hirokazu; Fukuhara, Noriko; Kitano, Toshiyuki; Ishikawa, Takayuki; Shibayama, Hirohiko; Choi, Ilseung; Hatake, Kiyohiko; Uchida, Toshiki; Nishikori, Momoko; Kinoshita, Tomohiro; Matsuno, Yoshihiro; et al.
Abstract : In this multicenter, single‐arm, phase II study, the efficacy and safety of ibrutinib were examined in Japanese patients with relapsed or refractory mantle cell lymphoma (MCL). Patients (age ≥20 years) with relapsed or refractory MCL who had progressed after receiving at least one prior treatment regimen, were enrolled. Patients were treated with oral ibrutinib (560 mg once daily; 28‐day cycle) until disease progression (or relapse), unacceptable toxicity, or study end. The primary end‐point was overall response rate. Secondary end‐points included duration of response (DOR), time to response, progression‐free survival (PFS), overall survival, and safety. Of the 16 patients who received treatment, 5 patients discontinued the study (progressive disease, 4; sepsis, 1). Median duration of ibrutinib exposure was 6.5 months (range, 2.8–8.3 months). The overall response rate was 87.5% (90% confidence interval, 65.6–97.7; complete response = 2 [12.5%]; partial response = 12 [75.0%]). Median time to response for all responders ( n = 14) was 1.8 months (range, 0.7–5.3 months). The median DOR and PFS were not estimable due to censoring (range: DOR, 1.1–6.4+ months; PFS, 2.8–8.0+ months). Overall survival data were immature due to the limited observation period. A total of 8/16 patients (50%) had at least one grade 3 adverse event (AE), and 5 (31.3%) patients reported serious AEs. The most commonly reported AEs were diarrhea and stomatitis (37.5% each), platelet count decrease (31.3%), and anemia (25%). Overall, orally administered single agent ibrutinib was efficacious with an acceptable safety profile in Japanese patients with relapsed or refractory MCL. Clinical trial registration NCT02169180 (ClinicalTrials.gov). Abstract : The aim of this study was to evaluate the efficacy and safety of ibrutinib in Japanese patients with relapsed or refractory MCL. The orally administered single agent ibrutinib was found to be efficacious with acceptable safety profile in Japanese patients with relapsed or refractory MCL.